From the Judaean Desert to the Great Sea: Qumran in a Mediterranean Context - Mizzi, Dennis (Dead Sea discoveries, 2017)
The time when Qumran was studied in splendid isolation is long gone, but much work remains to be done when it comes to situating the site in its wider context. In this paper, Qumran is contextualized, on the one hand, within the larger ecological history of the Mediterranean and, on the other, within the Mediterranean world of classical antiquity. Questions regarding the functions of the Qumran settlement are addressed from the perspective of “marginal zones” in the Mediterranean, which provides an ideal backdrop through which to illumine aspects of daily life at Qumran. Furthermore, it is shown how comparative case studies from the Graeco-Roman Mediterranean help us to nuance the discussion concerning “Hellenization” or “Romanization” with regard to Qumran. Finally, a new understanding of L4, which is here interpreted primarily as a dining room, is proposed on the basis of archaeological parallels from the Graeco-Roman world. A pan-Mediterranean perspective, therefore, allows us to generate new insights on old questions and novel interpretations.